Urgensi Kompetensi Digital Guru Dalam Pembelajaran PAI di SMK NU Lamongan - Mauidlotul Hunaidah; Ikmal Hepi Ikmal (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2023)
This research seeks to explain the digital competence of teachers in learning and the urgency of digital competency for PAI learning. This research uses a qualitative descriptive approach and uses the instruments of interviews, documentation, and observation. The subject of this research is SMK NU Lamongan. As for information, PAI teacher The research revealed four core digital competencies to possess: information, communication, content creation, and security. Digitally competent teachers can develop learning by leveraging technology without neglecting pedagogy. Increased digital competence among teachers requires training, certification, and self-development through education and training. The use of digital media in learning helps teachers and learners face the challenges of digital competence, but there is still a lack of understanding of technology, especially among Islamic teachers. The digital competence of teachers at SMK NU Lamongan is very important in the implementation of PAI learning, which involves learning goals, materials, strategies, and evaluations. The aim of PAI learning is to increase the fearfulness and goodwill of the students. Teachers need to master digital competencies in order to be able to effectively use technology in PAI learning